충남 석탄화력발전소 주변 지역 대기오염 영향 분석 - 김수향(Su-Hyang Kim); 박세찬(Sechan Park); 황규철(Kyucheol Hwang); 최영남(Young-Nam Choi); 이상신(Sang Sin Lee); 박선환(Sunhwan Park); 이가혜(Gahye Lee); 김정호(Jeongho Kim); 노수진(Sujin Noh); 김종범(Jong Bum Kim) (한국대기환경학회지(국문), 2024)
In this study, we analyzed the impact of air pollutants caused by a coal-fired power plants located in Chungnam. The Chungnam region is characterized by diverse large-scale emission facilities, particularly notable for coal-fired power plants emitting noteworthy quantities of air pollutants, including PM2.5, SO2, and NO2. For the analysis, we conducted modeling using the WRF-SMOKE-CMAQ system, utilizing emission data from the Clean Air Policy Support System (CAPSS) in 2019 was used. The modeling focused on Boryeong, Dangjin, and Taean, where coal-fired power plants are situated. To assess changes in concentration resulting from emission variations, the study used the Brute Force Method (BFM) and the Significant Impact Levels (SILs), developed by the United States Environmental Protection Agency (EPA). As a result of the emission analysis, it was found that air pollutant emissions in Chungnam were gradually decreasing, with significant reductions noted in Dangjin, Boryeong, and Taean. Analyzing the influence of surrounding areas on the modeling target areas revealed that the impact in Dangjin and Taean was relatively small, likely due to the wind trajectory being pushed from inland to the coast. Conversely, Boryeong had the most significant influence on its surrounding areas, with the most affected regions being Boryeong, Hongseong, and Yesan. KCI Citation Count: 1